2022
DOI: 10.3390/cancers14112775
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Response and Immune Biomarker Assessment in Non-Small-Cell Lung Carcinoma Receiving Neoadjuvant Immune Checkpoint Inhibitors

Abstract: Lung cancer is the leading cause of cancer incidence and mortality worldwide. Adjuvant and neoadjuvant chemotherapy have been used in the perioperative setting of non-small-cell carcinoma (NSCLC); however, the five-year survival rate only improves by about 5%. Neoadjuvant treatment with immune checkpoint inhibitors (ICIs) has become significant due to improved survival in advanced NSCLC patients treated with immunotherapy agents. The assessment of pathology response has been proposed as a surrogate indicator o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 129 publications
0
9
0
Order By: Relevance
“…MPR was defined as residual viable tumor cells in the primary tumor bed and sampled lymph nodes. MPR was reported both as a continuous variable and using the 10% cut-off, whereas pCR was defined as the complete absence of residual viable tumor cells in the primary tumor ( 8 , 9 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MPR was defined as residual viable tumor cells in the primary tumor bed and sampled lymph nodes. MPR was reported both as a continuous variable and using the 10% cut-off, whereas pCR was defined as the complete absence of residual viable tumor cells in the primary tumor ( 8 , 9 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, there are no established guidelines about the assessment of response to neoadjuvant therapy on resected lung cancer specimens. Over the years, different approaches have been used to assess pathological response, including pathological complete response (pCR) and major pathological response (MPR) ( 8 , 9 ). Previous studies have suggested a positive association between pathological response, mainly pCR, and clinical outcome of patients.…”
Section: Introductionmentioning
confidence: 99%
“…This is partly due to the lack of sensitive detection methods for NSCLC ( 5 ). Thus, it is crucial that the biomarkers of NSCLC be explored to improve the 5-year survival rate ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this Special Issue, we have brought together several articles focusing on recent topics related to lung cancer in the fields of fundamental, translational, and clinical research [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Basic research studies are essential to improve our knowledge of lung cancer carcinogenesis.…”
mentioning
confidence: 99%
“…Therefore, discoveries from these basic studies can help to develop future therapeutics or new diagnostics, prognostics, or predictive biomarkers [ 5 , 8 , 11 , 12 ]. In particular, tissue and circulating biomarkers from the coding and non-coding regions of the genome that are predictive of the response or resistance to different immunotherapies or targeted therapies are currently being evaluated or used in clinical trials or, more recently, in daily practice [ 1 , 2 , 10 , 13 , 14 , 15 , 16 , 17 ]. Certain biomarkers are also being tested but may be envisaged as optimizing approaches to precision medicine for NSCLC patients [ 5 , 7 , 18 ].…”
mentioning
confidence: 99%